2018
DOI: 10.1038/s41598-018-29558-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anaemia, Haemolysis, Inflammation and Haem Oxygenase-1 at Admission with Sepsis: a pilot study

Abstract: Upregulation of haem oxygenase-1 (HO-1), due to haemolysis and/or inflammation, can lead to impaired immune function. Anaemia is common among sepsis patients, but the consequences of sepsis-associated anaemia are poorly understood. Here, our objective was to determine the prevalence and extent of anaemia, haemolysis, inflammation, and HO-1 induction after early hospital admission. We hypothesised that inflammation- or infection-induced haemolysis contributes to sepsis-associated anaemia and that this will lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…In other words, in addition to defining the pathways leading to neutrophil dysfunction, we also need to identify the point at which the balance tips from these being host protective to increasing the risk to invasive NTS. Importantly, these pathways may contribute to severe bacterial disease even in the absence of malaria infections: in sepsis patients, we have observed that raised concentrations of heme, HO‐1, and IL‐10 are positively correlated with disease severity and mortality . Also, while “invasive” NTS is seen in immunocompromised hosts (such as those with malaria infection), it remains unclear if this is due to increased intestinal invasion, increased dissemination from draining lymph nodes, failure to control systemic bacterial replication, or a combination of any of these.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In other words, in addition to defining the pathways leading to neutrophil dysfunction, we also need to identify the point at which the balance tips from these being host protective to increasing the risk to invasive NTS. Importantly, these pathways may contribute to severe bacterial disease even in the absence of malaria infections: in sepsis patients, we have observed that raised concentrations of heme, HO‐1, and IL‐10 are positively correlated with disease severity and mortality . Also, while “invasive” NTS is seen in immunocompromised hosts (such as those with malaria infection), it remains unclear if this is due to increased intestinal invasion, increased dissemination from draining lymph nodes, failure to control systemic bacterial replication, or a combination of any of these.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, these pathways may contribute to severe bacterial disease even in the absence of malaria infections: in sepsis patients, we have observed that raised concentrations of heme, HO-1, and IL-10 are positively correlated with disease severity and mortality. 82…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes are crucial as they deliver oxygen from lungs to tissues. Sepsis is characterized by a reduction of the red blood cell count and a rapid rise in the WBC count 28,51 . We found that narciclasine could normalize the changes in most of these hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Narciclasine reduces the inflammatory anemia in neonatal rats with sepsis. The development of anemia is common during sepsis and highly prevalent in intensive care patients with high risk of sepsis 28 . We analyzed the whole blood parameters which revealed a significant reduction of RBC, hemoglobin and .…”
Section: Narciclasine Treatment Reduced the Liver Inflammation And Inmentioning
confidence: 99%
“…Ekregbesis and colleagues [83] tested the hypothesis that inflammation-or infection-associated hemolysis contributes to sepsis-associated anemia and also leads to detectable HO1 in plasma. Hemopexin levels were used as one of several parameters of hemolysis.…”
Section: Hpx As a Biomarker For Sepsismentioning
confidence: 99%